Analiza kinematike toka za utripajočim profilom spremenljive geometrijske oblike z uporabo računalniške vizualizacije - Širok, Brane (Strojniški vestnik, 2000)
In the fully developed airflow of a non-return subsonic wind tunnel using flow visualization and a digital image-processing method, an experimental study of the flow kinematics along and behind a hollow NACA 4416 adaptive airfoil at Reynolds number Re=1000 was performed. The study was performed in two parts: first the observation of flow transformation at temporal stationary changes of the air foil shape was performed, and the second part of the analysis focused on the transformation of the flow at periodic time-pulsating airfoil deformations. With the help of the computer-aided visualization method, structural flow changes were investigated, i.e. variations of the wake frequency response and respective amplitudes depending on the airfoil pulsation frequency. Results show that periodic changes of the airfoil shape have an affect on the flow structure along and behind the airflow, i.e. the amplitude and frequency of the wake, and the location of a separation point. There may exist possibilities for adaptive flow kinematics variation along and behind the airfoil.
Keywords: kinematika toka; analize tokov; strukture tokov; vizualizacija računalniška; vetrovniki; kinematika; tokovi; analiza